Stereotypical humour in the sitcom "Will and Grace" - Taufiq, Rizal (LITERA, 2023)
Stereotypes have often been associated with negative outcomes such as discrimination, prejudice, and bias. Nonetheless, this study investigates the potential for humour within stereotypical discourse in a sitcom. Through an analysis of humorous language used in sitcom, this research aims to uncover ways in which stereotypical utterances might bring about laughter as an outcome. Using the data from seven U.S. sitcom Will and Grace episodes throughout the eighth season, I generated the data from the show's transcript. I analysed how two characters, a white American woman and her maid, communicate with each other with a content analysis approach to categorize the different themes of humour presented in the seven chosen episodes. To determine of what is considered to be humorous utterances, I used the audience's laughter as the marker (Messerli 2016). The research demonstrated that the use of stereotypical humor involves exploiting the preconceived notions about another party's country of origin, physical appearance, and cognitive capacity. Further, my findings showed that an individual with higher power often performed stereotypical humour towards that with less power, while Holmes et al. (2003) saw humour as a linguistic technique for people who lacked power to establish a favourable image of themselves by challenging authority. Ultimately, this research promises to advance our understanding of the complex relationship between humour, stereotyping, and societal attitudes.